Synchronization of breathing and aiming skills as a basis for training rifle shooters at a moving target - Ilyakhina, O. Yu.; Kadutskaya, L. A.; Domracheva, E. Yu. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a pedagogical model for training rifle shooters at a moving target based on the synchronization of breathing and aiming skills.